Correlation of clinical, cytological, sonological diagnosis with histopathological diagnosis in cases of clinically diagnosed solitary thyroid nodule - Sachin, Idoor D.; Omprakash, Muruganathan; Amarendra, Pasham (International Surgery Journal, 2019)
Background: Thyroid disorders are highly prevalent in India. Clinical examination although very accurate, is inadequate in some areas. Ultrasound is most sensitive method for detection, while FNAC is most accurate method for evaluation of thyroid nodules. Both are used along with clinical examination but have drawbacks and final answer to this problem is elusive. Hence this study was planned to evaluate the usefulness of clinical examination, FNAC and USG in managing thyroid nodule. Methods: Hundred patients with clinically solitary thyroid nodule were included. USG and FNAC of thyroid were conducted. They were operated and specimen was sent for histopathological examination (HPE). Histopathology reports were correlated with USG and FNAC. Results: The commonest age group with thyroid pathology was 31-40 years. Majority of patients were females. All patients presented with swelling in anterior neck. Majority of patients presented between 6 months to 3 years. Consistency of nodule was firm in 88 patients and hard in 12. On USG, 70 cases were benign, 25 malignant and 5 suspicious while, on FNAC, 61 had benign lesions, 29 suspicious and 10 malignant. Commonest surgery was hemithyroidectomy. Most common lesion was benign follicular adenoma by HPE. Conclusions: Majority of patients were females aged 31-40 years with swelling in anterior neck. Duration of swelling prior to presentation was 6 months to 3 years. Incidence of malignancy in solitary nodule of thyroid was 18%. On FNAC majority of the lesions were benign. The sensitivity and specificity of FNAC was 74.3% and 100% while for USG was 73% and 85.3% respectively.